Tight Junction Assembly Ensures Maintenance of Pregnancy during Embryogenesis in a Mouse Model - Jeong, Yelin; Choi, Inchul (Journal of animal reproduction & biotechnology (Online), 2019)
Recent studies showed that tight junctions (TJs) integrity and assembly are required for blastocyst development in mouse and pig models. However, the biological functions of TJs associated with embryo implantation and maintenance of pregnancy were not investigated yet. To examine whether disrupted TJs affect further embryo development, we employed RNAi approach and inhibitor treatment. The embryos were injected with Cxadr (Coxsackievirus and adenovirus receptor) siRNA for knock down (KD) and treated with Adam10 (A Disintegrin and Metalloproteinase specific inhibitor 10; GI254023X; SI). We compared blastocyst development and paracellular sealing assay using FITC dextran uptake between control and KD or SI embryos. Finally, we transferred control and Cxadr KD or Adam 10 SI treated blastocyst to uteri of recipients. Cxadr KD and Adam 10 SI showed lower blastocyst development and more permeable to FITC-dextran. Moreover, we observed that half of KD and inhibited embryos failed to maintain pregnancies after the second trimester. Our findings suggested that TJs integrity is required for the maintenance of pregnancy and can be used as a selective marker for the successful application of assisted reproduction technologies.